Risk Assessment of The Use of Colistin Sulfate In Broiler Due To Escherichia coli Resistance In Broiler Flocks - Maria Fatima Palupi; Etih Sudarnika; I Wayan Teguh Wibawan; Huda Shalahudin Darusman; Hera Maheshwari (Acta VETERINARIA Indonesiana, 2019)
The risk assessment of antimicrobial resistance is very important to determine the risk of decreasing antimicrobial efficacy can be used as a basis for policymakers in allowing or prohibiting the use of an antimicrobial. This study aims to assess the risk of using colistin against E. coli resistance in the broiler flock. Risk assessment is carried out qualitatively using primary data, interviews, and secondary data. To obtain primary data various studies were carried out including monitoring the prevalence of colistin-resistant E. coli and mcr-1 also mcr-2 genes in broiler flocks, mcr-1 gene transfer from E. coli to Salmonella Enteritidis, mcr-1 gene sequencing, mutant selection windows of colistin against E. coli, and also multiresistant of E. coli colistin-resistant. Assessment of the risk of E. coli colistin-resistant in the broiler flocks through direct contact with live broiler flock environment with the resulting assessment is a medium risk with low uncertainty. Since colistin sulfate is very critically important for humans, the reduced use of colistin sulfate in animal production is necessary to reduce the risk of resistance. Reducing the use of colistin sulfate requires the collaboration of various sectors such as the government, veterinary drugs industries, farmers, and consumers.